Trapping flocking particles with asymmetric obstacles. Issue 20 (9th March 2020) - Martinez, Raul; Alarcon, Francisco; Aragones, Juan Luis; Valeriani, Chantal
Abstract : Asymmetric obstacles can be exploited to direct the motion and induce sorting of run-and-tumble particles. Abstract : Asymmetric obstacles can be exploited to direct the motion and induce sorting of run-and-tumble particles. In this work, we show that flocking particles which follow the Vicsek model aligning rules experience collective trapping in the presence of a wall of funnels made of chevrons, concentrating at the opposite side of the wall of funnels to run-and-tumble particles. Flocking particles can be completely trapped or exhibit a dynamical trapping behaviour; these two regimes open the door to the design of a system with two perpendicular flows of active particles. This systematic study broadens our understanding of the emergence of collective motion of microorganisms in confined environments and directs the design of new microfluidic devices able to control these collective behaviours.